The effect of corporate social responsibility on companies' profitability in Sibu, Sarawak - Ling, Allen Han Wei (Universiti Malaysia Sarawak (UNIMAS), 2012)
The research objectives in this study are i) to investigate the implications of corporate social responsibility on profitability of Sibu companies, ii) to discover the nature of CSR activities undertaken by companies in Sibu, iii) to identify the CSR economic drivers those stimulate CSR activities among Sibu companies, iv) to show the factors stimulating corporate social responsibility practices among Sibu companies, and v) to determine the effect of CSR reporting and disclosure on the profitabiJity of Sibu companies.) 180 respondents are selected among the companies in Sibu but only 150 questionnaires are been collected. Four theoretical relationships are developed to examine the relationship between the related variables. Findings show that I) there is a negative relationsh ip between CSR and corporate performance under the trade~off hypothesis, 2) there is no relationship between CSR and firm's profitability under the supply and demand hypothesis, 3) there is a positive relationship between CSR and firm financial performance under social impact hypothesis, and 4) there is a negative relationship between CSR and firm's profitability under theory of stakeholder. CSR includes CSR activities, factors stimulating CSR, and CSR economic drivers. Regression model is developed to link CSR elements to corporate profitability. The CSR activities perceived to be relevant to the companies are corporate philanthropy, caused related marketing and sponsorship. Besides, the factors and economic drivers will be addressed based on the four dimensions; employees, environment, community at large and customers .